Computed Intranasal Spray Penetration: Comparisons Before and After Nasal Surgery - Frank, Dennis O. (2012)
BACKGROUND: Quantitative methods for comparing intranasal drug delivery efficiencies pre- and postoperatively have not been fully utilized. The objective of this study is to use computational fluid dynamics techniques to evaluate aqueous nasal spray penetration efficiencies before and after surgical correction of intranasal anatomic deformities. METHODS: Ten three-dimensional models of the nasal cavities were created from pre- and postoperative computed tomography scans in five subjects. Spray simulations were conducted using a particle size distribution ranging from 10–110μm, a spray speed of 3m/s, plume angle of 68°, and with steady state, resting inspiratory airflow present. Two different nozzle positions were compared. Statistical analysis was conducted using Student T-test for matched pairs. RESULTS: On the obstructed side, posterior particle deposition after surgery increased by 118% and was statistically significant (p-value=0.036), while anterior particle deposition decreased by 13% and was also statistically significant (p-value=0.020). The fraction of particles that by-passed the airways either pre- or post-operatively was less than 5%. Posterior particle deposition differences between obstructed and contralateral sides of the airways were 113% and 30% for pre- and post-surgery, respectively. Results showed that nozzle positions can influence spray delivery. CONCLUSIONS: Simulations predicted that surgical correction of nasal anatomic deformities can improve spray penetration to areas where medications can have greater effect. Particle deposition patterns between both sides of the airways are more evenly distributed after surgery. These findings suggest that correcting anatomic deformities may improve intranasal medication delivery. For enhanced particle penetration, patients with nasal deformities may explore different nozzle positions.